A Survey on Bio-based Food Packaging Material About the Presence and Migration of Flame Retardants - Simonetti, Giulia; Acquaviva, Luca; Buiarelli, Francesca; Riccardi, Carmela; Pomata, Donatella; Di Filippo, Patrizia (Current Analytical Chemistry, 2023)
Introduction: The present work fits in the context of verifying the safety of some food contact materials (FCMs) declared sustainable, checking for the presence of different classes of contaminants and their possible migration. Background: Alternative packaging materials have started to step in the market in substitution to plastic for several years. Most of them come from natural, biological sources to meet biodegradability and compostability. Nevertheless, some contaminants can be present and concerning for human health. Objective: To pursue the goal, we focused on brominated flame retardants, in particular new brominated flame retardants and bromophenols, as they are considered emerging contaminants, and no legislation has been enacted yet. Methods: After the evaluation of their presence in the seven investigated samples, we adopted migration tests into proper simulants recommended by the legislation. The analyses were carried out both by gas chromatography-mass spectrometry and by high-performance liquid chromatography-tandem mass spectrometry. Results: All the items taken into consideration contained detectable concentrations of the investigated compounds. The total amount of new brominated flame retardants were considered irrelevant to proceed with the migration study, whereas the migration of bromophenols was studied in deep due to the greater amount present. Conclusion: In overall, the findings obtained on real samples showed that, except in one case the percentage of chemicals migration measured was very low, to be considered not concerning for human health in most of the cases.
Keywords: simulants